ANALYZING THE IMPACT OF CAPITAL STRUCTURE AND GOVERNANCE ON THE RISK PROFILE AND FINANCIAL STABILITY OF ISLAMIC BANKS IN INDONESIA - Hendrik Tri Oktaviansyah; Sjafruddin; Robby Reza Zulfikri (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
This study aims to examine the impact of Islamic capital structure and governance on risk and the health of Islamic banks. This research employs a quantitative methodology. The sample consists of 10 Islamic banks in Indonesia, analyzed over a 10-year period from 2011 to 2020. The data used in this study includes both primary and secondary data. Primary data was collected through questionnaires distributed to various management parties related to the health of Islamic banks, using the ANGELS approach. Secondary data consists of financial reports from Islamic banks over the 10-year period. The findings indicate that capital structure has a positive impact on the health of Islamic banks, while governance and risk also have a significant positive effect on the health of Islamic banks. The originality of this study lies in assessing the health of Islamic banks using the ANGELS approach, as the CAMELS and RGEC methods have been frequently used by Islamic banks for health assessments. This study contributes to the understanding of the importance of capital structure for Islamic banks in Indonesia to improve their health.